Dynamic simulation of breast behaviour during different activities based on finite element modelling of multiple components of breast - Jiazhen Chen; Zejun Zhong; Yue Sun; Joanne Yip; Kit-lun Yick (Scientific Reports)
Abstract This study presents an advanced dynamic finite element (FE) model of multiple components of the breast to examine the biomechanical impact of different types of physical activities and activity intensity on the breast tissues. Using 4D scanning and motion capture technologies, dynamic data are collected during different activities. The accuracy of the FE model is verified based on relative mean absolute error (RMAE), and optimal material parameters are identified by using a validated stepwise grid search method. The comparative analysis reveals that jumping rope generates the highest stress on the breast components, followed by high knee skipping but running exerts the least amount of stress. A positive correlation between activity intensity and stress is observed for running and jumping rope, while high knee skipping shows a peak in stress after a certain threshold. The magnitude of the stress distribution and effect of activity intensity on the stress experienced by the breast internal components are in ascending order: the glandular tissues, pectoralis major muscles, adipose tissues, and Cooper’s ligaments, thus highlighting the different biomechanical response of these breast components to dynamic stress. The insights from this study have significant implications for sports bra design, rehabilitation protocols, and exercise customisation with the aim to reduce the risk of injury during breast motion.